التحديات التي تواجه أساتذة التربية البدنية والرياضية في تنفيذ منهاج الجيل الثاني في الطور الابتدائي - صيودة فوزي (My University, 2024)
الملخص: 1/ باللغة العربية: هدفت الدراسة الحالية للتعرف على مستوى التحديات التي تواجه أساتذة التربية البدنية والرياضية في تنفيذ منهاج الجيل الثاني في الطور الابتدائي في ولاية سوق اهراس ( مقاطعة 01 )، واستخدم الباحث المنهج الوصفي لملائمته لإجراءات الدراسة ولتحقيق ذلك أجريت الدراسة على عينة عشوائية بسيطة قوامها ( 50 ) أستاذ من أساتذة التربية البدنية والرياضية في الطور ، واستخدم الاستبيان كاداة لجمع البيانات، كما استخد الباحث برنامج (spss) لحساب معامل ارتباط بيرسون، اختبار شابيرو ويلك واختبار (ت) لعينيتين، وتوصل الباحث إلى النتائج التالية: -مستوى التحديات التي تواجه أساتذة التربية البدنية والرياضية للطور الابتدائي في ولاية سوق اهراس ( مقاطعة 01 ) كان متوسطا، حيث كانت اكثر التحديات على مجال الامكانيات المادية، في حين جاء اقل التحديات على مجال تكوين الاساتذة، وأوصت الدراسة بعدة توصيات من أهمها: - ضرورة ان تقوم وزارة التربية والتعليم بالاهتمام بالإمكانيات المادية متمثلة في ( منشات رياضية، رسائل رياضية وبيداغوجية) - توفير ميزانية خاصة بمادة التربية البدنية والرياضية ومستقلة عن ميزانية باقي المواد، كذلك ضرورة تخفيض عدد التلاميذ في القسم كذلك زيادة الدورات التكوينية للأساتذة لزيادة رصيدهم المعرفي للتحدي لهذه التحديات والتأقلم معها وإيجاد الحلول المناسبة للعمل في أحسن الظروف. abstract : The current study aimed to identify the level of challenges facing teachers of physical education and sports in implementing the second generation curriculum in the primary stage in the state of Souk Ahras (Province 01). The researcher used the descriptive approach to suit the study procedures. To achieve this, the study was conducted on a simple random sample of (50) teachers.The questionnaire was used as a tool for collecting data, and the researcher used the SPSS program to calculate the Pearson correlation coefficient, the Shapiro-Wilk test, and the two-sample t-test. The researcher reached the following results: The level of challenges facing teachers of primary school physical education and sports in the state of Souk Ahras (District 01) was moderate, as the most challenges were in the field of financial capabilities, while the least challenges were in the field of teacher training. The study recommended several recommendations, the most important of which are: - It is necessary for the Ministry of Education to pay attention to the financial capabilities represented in (sports facilities, sports and pedagogical messages) - Providing a special budget for physical education and sports, independent of the budget for the rest of the subjects, as well as the need to reduce the number of students in the department, as well as increasing the training courses for professors to increase their knowledge to challenge these challenges, adapt to them, and find appropriate solutions to work in the best conditions. Résumé: En français La présente étude visait à identifier le niveau de défis auxquels sont confrontés les enseignants d'éducation physique et sportive dans la mise en œuvre du programme de deuxième génération au niveau primaire dans l'État de Souk Ahras (Province 01). Le chercheur a utilisé l'approche descriptive pour s'adapter aux procédures d'étude. Pour y parvenir, l'étude a été menée sur un échantillon aléatoire simple de (50) enseignants. Le questionnaire a été utilisé comme outil de collecte de données, et le chercheur a utilisé le programme SPSS pour calculer le coefficient de corrélation de Pearson, le test de Shapiro-Wilk, et le test t à deux échantillons. Le chercheur a obtenu les résultats suivants : Le niveau de défis auxquels sont confrontés les enseignants d'éducation physique et sportive du primaire dans l'État de Souk Ahras (District 01) était modéré, car la plupart des défis concernaient le domaine des capacités financières, tandis que le moins de défis se situait dans le domaine de la formation des enseignants. L’étude recommande plusieurs recommandations, dont les plus importantes sont :  Il est nécessaire que le Ministère de l'Éducation soit attentif aux capacités financières représentées (installations sportives, messages sportifs et pédagogiques)  Prévoir un budget spécial pour l'éducation physique et sportive, indépendant du budget du reste des matières, ainsi que la nécessité de réduire le nombre d'étudiants dans le département, ainsi que d'augmenter les cours de formation des professeurs pour accroître leurs connaissances relever ces défis, s’y adapter et trouver les solutions adaptées pour travailler dans les meilleures conditions.
دراسة ميدانية على مستوىابتدائيات ولاية سوق اهراس
Keywords: le curriculum de la deuxième génération; les défis; le curriculum; la deuxième génération.; the second generation curriculum; challenges; the curriculum; the second generation.; منهاج الجيل الثاني; التحديات; المنهاج; الجيل الثاني